Online Game Service Providers Responbilities for Damages Sufficiented to Consumer - Firstza Maulana Krishna Syahputra; Endang Prasetyawati (Activa Yuris: Jurnal Hukum, 2024)
The purpose of this study is to find out and explain how the responsibility of online game service providers is for losses suffered by consumers and legal settlements carried out. Consumer protection is a term used to describe legal protection given to consumers in their efforts to meet their needs from things that can harm the consumers themselves. The problem that will be examined and analyzed in this research is how the responsibility of online game service providers to Law No. 8 of 1999 concerning Consumer Protection. This study uses a normative legal approach method in the form of a statutory and conceptual approach by using primary legal materials, namely laws and secondary legal materials, namely books and journals related to the discussion. The responsibilities of providers of online game services regarding Law No. 8 of 1999 Concerning Consumer Protection include the presence of responsibilities that are responsible for administrative and criminal responsibility, and there is civil responsibility for online game providers which is contained in Article 19 of the Law on Crime Protection. and Consuimein those who have Tangguing are responsible for damages for damages, Tangguing are responsible for compensation for damages for violations and Tangguing are responsible for compensation for losses for consumers. Based on this, the existence of defective goods and/or services is not the only basis for accountability for the provider of online game services. This means that the responsibilities of the provider of online game services cover all the disadvantages that consumers experience. And article 4 of the Consumer Protection Act explains the rights and beliefs of consumers. The results of the research show that the providers of online game services can answer their mistakes by paying compensation or deliberations to reach consensus